A mixed-methods investigation into the user experience of well-being applications - Smith, Catherine (2020)
Mobile technology, including applications, can offer a range of benefits as an intervention delivery method, such as cost-effectiveness and ease of access. Well-being interventions have been developed in order to support people who do not have a diagnosis of mental ill health, but who are still not flourishing or feel fully satisfied with their lives. Mobile technology could be the most suitable way of delivering these interventions, as they can be accessed anonymously by many people as and when they are needed, without using large amount of resources and contact time with mental health professionals. However, mobile technology can only be a successful delivery method if users are engaged with the applications.